Fis Is Essential for Yersinia pseudotuberculosis Virulence and Protects against Reactive Oxygen Species Produced by Phagocytic Cells during Infection. - Erin R Green; Stacie Clark; Gregory T Crimmins; Matthias Mack; Carol A Kumamoto; Joan Mecsas (PLoS Pathogens, 2016)
All three pathogenic Yersinia species share a conserved virulence plasmid that encodes a Type 3 Secretion System (T3SS) and its associated effector proteins. During mammalian infection, these effectors are injected into innate immune cells, where they block many bactericidal functions, including the production of reactive oxygen species (ROS). However, Y. pseudotuberculosis (Yptb) lacking the T3SS retains the ability to colonize host organs, demonstrating that chromosome-encoded factors are sufficient for growth within mammalian tissue sites. Previously we uncovered more than 30 chromosomal factors that contribute to growth of T3SS-deficient Yptb in livers. Here, a deep sequencing-based approach was used to validate and characterize the phenotype of 18 of these genes during infection by both WT and plasmid-deficient Yptb. Additionally, the fitness of these mutants was evaluated in immunocompromised mice to determine whether any genes contributed to defense against phagocytic cell restriction. Mutants containing deletions of the dusB-fis operon, which encodes the nucleoid associated protein Fis, were markedly attenuated in immunocompetent mice, but were restored for growth in mice lacking neutrophils and inflammatory monocytes, two of the major cell types responsible for restricting Yersinia infection. We determined that Fis was dispensable for secretion of T3SS effectors, but was essential for resisting ROS and regulated the transcription of several ROS-responsive genes. Strikingly, this protection was critical for virulence, as growth of ΔdusB-fis was restored in mice unable to produce ROS. These data support a model in which ROS generated by neutrophils and inflammatory monocytes that have not been translocated with T3SS effectors enter bacterial cells during infection, where their bactericidal effects are resisted in a Fis-dependent manner. This is the first report of the requirement for Fis during Yersinia infection and also highlights a novel mechanism by which Yptb defends against ROS in mammalian tissues.